2022
DOI: 10.21037/atm-22-2583
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylate cyclase (sGC) stimulator vericiguat alleviates myocardial ischemia-reperfusion injury by improving microcirculation

Abstract: Background: This study aimed to verify the effect of soluble guanylate cyclase (sGC) stimulator vericiguat on myocardial ischemia-reperfusion injury and explore its mechanism.Methods: A myocardial ischemia-reperfusion injury model of mice was established and intravenous administration was performed 2 minutes before reperfusion. Triphenyltetrazolium chloride (TTC) staining and echocardiography were used to verify the effect of vericiguat on myocardial ischemia-reperfusion injury in the infarct area, and immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…After the baseline experiments, vericiguat at a dose of 5 μmol/L was administrated to evaluate the effects of acute vericiguat therapy. As reported by Cai et al [ 11 ], vericiguat at a dose of 1 to 10 μmol/L is considered safe and capable of promoting an increase in cGMP in cardiomyocytes. The same pacing protocols for electrophysiological study and optical mapping were repeated 20 minutes after the start of vericiguat perfusion.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…After the baseline experiments, vericiguat at a dose of 5 μmol/L was administrated to evaluate the effects of acute vericiguat therapy. As reported by Cai et al [ 11 ], vericiguat at a dose of 1 to 10 μmol/L is considered safe and capable of promoting an increase in cGMP in cardiomyocytes. The same pacing protocols for electrophysiological study and optical mapping were repeated 20 minutes after the start of vericiguat perfusion.…”
Section: Methodsmentioning
confidence: 87%
“…According to a previous study [ 12 ], the EC 50 of vericiguat for sGC activation is 1.005 ± 0.145 mmol/L. Vericiguat at a dose of 1 to 10 μmol/L is considered safe and capable of promoting an increase in cGMP in cardiomyocytes [ 11 ]. Therefore, we chose a larger dose to ensure the pharmacological effects in the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…As a stimulator of sGC, vericiguat can not only stimulate sGC directly but also cooperate with NO, resulting in the increase of cGMP ( Kang and Lamb, 2022 ). Previous studies have shown that vericiguat of 3 mg/kg can significantly increase the content of cGMP in mice ( Cai et al, 2022 ). Our results show compared with the control group, the content of cGMP was decreased in the DOX group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 98%
“…Mice in the vericiguat-treated group received a gavage of vericiguat (MCE HY-16774) for two weeks prior to injection of DOX and continued until 72 h after the DOX injection. The dosage of vericiguat was set to 3 mg/kg/day, as used previously in other studies ( Follmann et al, 2017 ; Cai et al, 2022 ). Mice were monitored daily and then euthanized 72 h post-injection.…”
Section: Methodsmentioning
confidence: 99%
“…40 Research has shown that VIT can protect against oxidative stress-induced damage in neurons, reduce the risk of heart attack and stroke, and alleviate symptoms of inflammatory diseases such as rheumatoid arthritis and Crohn's disease. 41,42 SIRT1, an NAD+-dependent deacetylase, has been shown to protect cells from oxidative stress by regulating the expression of genes involved in antioxidant defense, inflammation, and cell survival. 43 In addition to its role in antioxidant defense, SIRT1 also plays a role in the regulation of cell metabolism, which can also be affected by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%